Privatization and Remunicipalization of Water Supply: A Global Research - Aikaterini Koumpli; Vasilis Kanakoudis (Environmental Sciences Proceedings, 2022)
The present study delves into the global issue of privatization and the remunicipalization of water services/suppliers with special reference to the case of Greece. Through the analysis of several successful and unsuccessful management practices of water services that have been implemented around the world, the article concludes with the proposed water supply model for Greece, and specifically for municipal water supply and sewerage companies (MWSSCs), through the application of the appropriate form of public–private partnerships (PPPs). The final proposal takes into account the weaknesses of the existing water supply systems in Greece, the social impact of recent privatization efforts, the current legal and institutional framework, and the economic special characteristics of our country.